Detection and Evaluation of Methicillin-Resistant Staphylococcus aureus by Duplex PCR (Al-Nahrain Journal of Science, 2013)
Staphylococcusaureusis avirulence pathogenic bacterium.Detection of methicillin-resistant S. aureus(MRSA) using conventional culture and biochemical methods is labor and time consuming. Many MRSA isolates are heterogeneously resistant to ß-lactams, for example only 1 daughter cell out of 104 to 106 cells appears phenotypically resistant when routine antimicrobial susceptibility tests are performed. In this work two genes were used for detection of MRSA in urine, boil and nasal swabs using conventional PCR, mecA gene (533bp) were used for detection of methicillin resistant and femA gene (318bp) were used for S.aureus identification. It was found that not all resistant S. aureus tested with disk diffusion method carry the mecA gene that caused the resistant phenomena there were only 55% of all MRSA carrying mecA gene while femA gene gave 100% positive for S. aureus and this will lead us to appoint that penicillin-bindingprotein 2a (PBP2a) produced by mecA gene is not the only cause of resistant phenomena.